Cutis 2021
DOI: 10.12788/cutis.0291
|View full text |Cite
|
Sign up to set email alerts
|

Results of Laboratory Monitoring in Patients Taking Isotretinoin for Acne

Abstract: Isotretinoin is one of the most effective drugs for the treatment of all forms of acne vulgaris. It has been suspected of causing alterations in lipids and liver enzymes. The aim of this retrospective study was to determine the prevalence of laboratory changes among 371 patients with acne receiving isotretinoin therapy. Each patient's medical records were evaluated to determine baseline alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol, and triglycerides (TGs) compared to leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“… 10 In contrast, Al Riyadh, KSA study demonstrated high TG levels over time (1.6%, 3.8%, and 4.4%) at baseline and first and second readings, respectively. 14 Another retrospective study of 415 patients also supported significant differences between TG measurements mostly between the second month (23.9%) and the fourth month (27.2%). 16 Many studies supported that high TG levels were associated with the third and sixth months of treatment.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“… 10 In contrast, Al Riyadh, KSA study demonstrated high TG levels over time (1.6%, 3.8%, and 4.4%) at baseline and first and second readings, respectively. 14 Another retrospective study of 415 patients also supported significant differences between TG measurements mostly between the second month (23.9%) and the fourth month (27.2%). 16 Many studies supported that high TG levels were associated with the third and sixth months of treatment.…”
Section: Discussionmentioning
confidence: 76%
“…10 On the other hand, a retrospective study in Al Riyadh, KSA of 386 patients had high TC baseline readings as well as 2 follow-up readings (12.1%, 21.8%, and 18.7%, respectively). 14 Also, a study done in Sakarya University, Turkey, found no relation statistically between the third and sixth months of treatment in all parameters including cholesterol and TG. 15 Regarding triglyceride level readings, we noticed that almost all the patients had a normal baseline (90.9%) and both second (95.5%) and last (94.3%) follow-up readings.…”
mentioning
confidence: 92%
“…Aunque el perfil de seguridad de la isotretinoina para el tratamiento de acné pareciera ser difícil (4) de sopesar , realmente la evidencia científica y recomendaciones de expertos sugieren que el monitoreo continuo no es útil, basados en que predominantemente solo los triglicéridos y pruebas de función hepática sufren alteraciones, pero estos se presentan en un porcentaje muy bajo de pacientes y no representan un riesgo considerable. Por el contrario, es necesario pensar en realizar intervenciones utilizando el mínimo de recursos, sobre todo en países de bajos y medianos ingresos, donde los sistemas de salud presentan numerosas barreras para garantizar acceso oportuno y eficaz a terapias especializadas.…”
Section: Estimado Editorunclassified
“…Results of retrospective study in 2021 concluded that changes in serum transaminase and lipid profiles are unlikely to occur when isotretinoin is used. However, physicians should be cautious when prescribing isotretinoin to individuals who have a history of aberrant results [22].…”
Section: Monitoring Of Isotretinoinmentioning
confidence: 99%